Clinical features and microbiology in 204 cases of septic arthritis in Malawian children. - Lavy, C; Thyoka, M; Pitani, A (2005)
We examined 204 children (137 boys and 67 girls) aged 12 years and under with septic arthritis. Their mean age was 31.1 months (1 to 144; SD 41.6). The most common joints affected were the knees and shoulders. Joints in the upper limb were affected more often in younger children and in the lower limb in those who were older. The mean age for an infection was 12 months in the shoulder and 73 months in the hip. The most common organisms cultured were species of Salmonella.